Exposure Conditions and Sensibility of the La Barra Community Face to Extreme Meteorological Phenomena - Durán-Solarte, Luz-Carina (2021)
This article analyses the vulnerability conditions of a fishing community facing the extreme meteorological phenomena aggravated by climate change. The methodology is qualitative, supported by geographic methods, based on the case study of the “La Barra afro-descendant community”, located in the Colombian Pacific Coast, in the mouth of San Juan River. As there is limited access to the community due to its geographical conditions, besides the biosecurity requirements due to the COVID-19 pandemic, a documentary analysis, as well as multi-temporal maps based on satellite images, show the spatial changes on the coastline of La Barra, during the years 2001, 2011 and 2019. In addition to the above, interviews with academic experts and community residents are conducted. The term “vulnerability” is understood from the school of thought of climate change science and adaptation research. It is concluded that the vulnerability not only depends on climatic stimuli but also on the racialized and marginalized conditions of Afro populations located in isolated rural territories. In that way, the social and political nature of the meteorological phenomena could transform them in catastrophic events for vulnerable populations.